2016
DOI: 10.1186/s40463-016-0170-2
|View full text |Cite
|
Sign up to set email alerts
|

Decision aid prototype development for parents considering adenotonsillectomy for their children with sleep disordered breathing

Abstract: BackgroundTo describe the process involved in developing a decision aid prototype for parents considering adenotonsillectomy for their children with sleep disordered breathing.MethodsA paper-based decision aid prototype was developed using the framework proposed by the International Patient Decision Aids Standards Collaborative. The decision aid focused on two main treatment options: watchful waiting and adenotonsillectomy. Usability was assessed with parents of pediatric patients and providers with qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…First, participants preferred the presentation of DAv2014, suggesting that appealing visuals (esthetics, colors, fonts) favoured acceptability and usability of a DA. This is consistent with other literature relating to evaluation of DAs, where authors report suggested changes to be made to their DAs in terms of font size (43), background colours (43) and colors in general (43)(44)(45)(46). According to these studies, participants dislike colors that are "flat", "uninteresting" or "somber".…”
Section: Discussionsupporting
confidence: 90%
“…First, participants preferred the presentation of DAv2014, suggesting that appealing visuals (esthetics, colors, fonts) favoured acceptability and usability of a DA. This is consistent with other literature relating to evaluation of DAs, where authors report suggested changes to be made to their DAs in terms of font size (43), background colours (43) and colors in general (43)(44)(45)(46). According to these studies, participants dislike colors that are "flat", "uninteresting" or "somber".…”
Section: Discussionsupporting
confidence: 90%
“…A steering committee, made up of clinicians, researchers, knowledge translation experts, and parents of pediatric patients, directed the development of the DA. The specific information within the DA was based on what was deemed important by the steering committee and was populated with information from a scoping literature review . Although the development process was laborious, the integration of stakeholder perspectives throughout has been shown to increase the likelihood that these tools will be adopted into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The specific information within the DA was based on what was deemed important by the steering committee and was populated with information from a scoping literature review. 18 Although the development process was laborious, the integration of stakeholder perspectives throughout has been shown to increase the likelihood that these tools will be adopted into clinical practice. Additional stages upon completion of the IPDAS framework include assessing the effectiveness of the DA through a rigorous randomized controlled trial and evaluating dissemination methods to facilitate implementation into routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decision aid example is provided in Figure 1 . 21 It contains not only a brief description of pediatric obstructive sleep apnea, management options, and the associated risks and benefits but also a section to help clarify family values. Employing option grids and decision aids before, during, and/or after appointments has demonstrated tangible improvements in informed consent, health-related quality of life, patient knowledge, and decisional conflict.…”
Section: How Do Option Grids and Decision Aids Relate To Sdm?mentioning
confidence: 99%